2022
DOI: 10.1029/2021jb023002
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Hypothesis That Syn‐Collisional Felsic Magmatism Contributes to Continental Crustal Growth Via Deep Learning Modeling and Principal Component Analysis of Big Geochemical Datasets

Abstract: The origin and evolution of Earth's continental crust play a fundamental role in shaping the planet (e.g., Mole et al., 2014), which can be simply embodied by its modification of the compositions of the upper mantle, ocean water, and atmosphere (e.g., Hawkesworth et al., 2019). However, our knowledge remains incomplete on such questions as when and how the continental crust was formed, how the crustal volume has changed (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…These are the problems that do not have existing accepted solutions, rely heavily on judgments of highly experienced experts, yet could lead to the most profound scientific insights if investigated properly. A few studies explore the promise of ML in multi‐disciplinary data integration for predicting drought behavior in the Colorado River Basin based on various Earth System Models (Talsma et al., 2022), for predicting sea surface variabilities in the South China Sea (Shao et al., 2021), for geothermal heat flow prediction from multiple geophysical and geological datasets (Lösing & Ebbing, 2021), for identifying volcano's transition from non‐eruptive to eruptive states (Manley et al., 2021), for understanding the geodynamic history using geochemical data (Jorgenson et al., 2022; X. Lin et al., 2022; X. Li & Zhang, 2022; Saha et al., 2021; Thomson et al., 2021; Y. Wang et al., 2021), and for characterizing geodetic signals by their sources (Hu et al., 2021). Albert (2022) uses an unsupervised deep NN structure to predict future atmospheric structures from past measurements to enable infrasound propagation modeling.…”
Section: Highlightsmentioning
confidence: 99%
“…These are the problems that do not have existing accepted solutions, rely heavily on judgments of highly experienced experts, yet could lead to the most profound scientific insights if investigated properly. A few studies explore the promise of ML in multi‐disciplinary data integration for predicting drought behavior in the Colorado River Basin based on various Earth System Models (Talsma et al., 2022), for predicting sea surface variabilities in the South China Sea (Shao et al., 2021), for geothermal heat flow prediction from multiple geophysical and geological datasets (Lösing & Ebbing, 2021), for identifying volcano's transition from non‐eruptive to eruptive states (Manley et al., 2021), for understanding the geodynamic history using geochemical data (Jorgenson et al., 2022; X. Lin et al., 2022; X. Li & Zhang, 2022; Saha et al., 2021; Thomson et al., 2021; Y. Wang et al., 2021), and for characterizing geodetic signals by their sources (Hu et al., 2021). Albert (2022) uses an unsupervised deep NN structure to predict future atmospheric structures from past measurements to enable infrasound propagation modeling.…”
Section: Highlightsmentioning
confidence: 99%
“…Recently, several studies have demonstrated that the data-driven machine learning methods can be powerful tools for solving complex problems in mineralogy, petrology, and geochemistry (Petrelli and Perugini 2016;Chen et al 2021;Huang et al 2022;Lin et al 2022;Nathwani et al 2022;Qin et al 2022;Wang et al 2022;Zou et al 2022), and for the construction of thermobarometers (Petrelli et al 2020;Higgins et al 2022;Jorgenson et al 2022;Li and Zhang 2022), without having any a priori knowledge. These research advances suggest that the machine learning method has the potential to be used for calibrating a mineral chemical-based oxybarometer.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of big geodata, many research topics and methods have been pursued to address particular issues associated with quantitative geology (Wu and Liu, 2019). Studies show that geoscientists are able to study and solve related geological problems by deep mining large geological datasets (Lin et al, 2022) Among all big data analysis techniques, machine learning (particularly deep learning) has been widely used in the geoscience community, and interesting predictive models have been built. By adopting machine learning, we have uncovered a new approach for interrogating geological big data (Luo and Zhang, 2019).…”
Section: Introductionmentioning
confidence: 99%